Determining erosion rates in Allchar (Macedonia) to revive the lorandite neutrino experiment. (31st May 2018) - Vermeesch, Pieter; Rittner, Martin; Schimmelpfennig, Irene; Benedetti, Lucilla; Team, ASTER
Abstract : 205 Tl in the lorandite (TiAsS2 ) mine of Allchar (Majdan, FYR Macedonia) is transformed to 205 Pb by cosmic ray reactions with muons and neutrinos. At depths of more than 300 m, muogenic production would be sufficiently low for the 4.3 Ma old lorandite deposit to be used as a natural neutrino detector. Unfortunately, the Allchar deposit currently sits at a depth of only 120 m below the surface, apparently making the lorandite experiment technically infeasible. We here present 25 erosion rate estimates for the Allchar area using in situ produced cosmogenic 36 Cl in carbonates and 10 Be in alluvial quartz. The new measurements suggest long-term erosion rates of 100–120 m Ma −1 in the silicate lithologies that are found at the higher elevations of the Majdanksa River valley, and 200–280 m Ma −1 in the underlying marbles and dolomites. These values indicate that the lorandite deposit has spent most of its existence at depths of more than 400 m, sufficient for the neutrinogenic 205 Pb component to dominate the muon contribution. Our results suggest that this unique particle physics experiment is theoretically feasible and merits further development.